C1q/TNF‐related protein 6 (CTRP6) attenuates renal ischaemia‐reperfusion injury through the activation of PI3K/Akt signalling pathway. (26th February 2020) - Xiang, Heli; Xue, Wujun; Li, Yang; Zheng, Jin; Ding, Chenguang; Dou, Meng; Wu, Xiaoyan
Abstract: C1q/TNF‐related protein 6 (CTRP6) is a member of the CTRP family that has been reported to exhibit a nephroprotective effect. However, the role of CTRP6 in renal ischaemia/reperfusion (I/R) injury (IRI) remains unclear. In the present study, we aimed to explore the protective effect of CTRP6 in renal IRI and the potential mechanism. We found that CTRP6 expression was markedly decreased in the kidneys of mice subjected to I/R and HK‐2 cells in response to hypoxia/reoxygenation (H/R) stimulation. Recombinant CTRP6 protein protected against renal I/R injury by the reduction of blood urea nitrogen (BUN) and creatinine levels. The increased production of ROS and malondialdehyde (MDA), as well the decreased activities of glutathione peroxidase (GPx) and superoxide dismutase (SOD) caused by H/R induction were mitigated by CTRP6 in HK‐2 cells. The caspase‐3 activity and apoptotic rate were both decreased in CTRP6‐overexpressing HK‐2 cells. In addition, we also found that knockdown of CTRP6 aggravated H/R‐caused oxidative stress and cell apoptosis in HK‐2 cells. Moreover, CTRP6 overexpression enhanced the H/R‐stimulated activation of PI3K/Akt pathway in HK‐2 cells. Inhibition of PI3K reversed the nephroprotective effects of CTRP6 in HK‐2 cells. Taken together, CTRP6 exerted protective effects against H/R‐caused oxidative injury in HK‐2 cells via activating the PI3K/Akt pathway.